INOVASI DAN EFEKTIVITAS SISTEM ADMINISTRASI AKADEMIK HYBRID PASCA PANDEMI DI JURUSAN MPI UIN SUNAN GUNUNG DJATI BANDUNG - Inayah, Jihan Nur; Irawan, Irawan; Kamaliyah, Afnie Nur; Ahmad, Chyril Futuhana (Pascasarjana Universitas Pendidikan Ganesha, 2025)
The Islamic Education Management Department at UIN Sunan Gunung Djati Bandung is one of the departments that has implemented digitalization in its academic administration system. Before the pandemic, most administrative activities were carried out manually and face-to-face. The purpose of this study is to comprehensively describe the changes and innovations that have occurred in the academic administration of the Islamic Education Management Department, while also uncovering various innovations implemented to support the effectiveness of post-pandemic academic services. The research method used is qualitative with a descriptive approach. This study was conducted at the Islamic Education Management Department, UIN Sunan Gunung Djati Bandung. Data were obtained through interviews with MPI department staff directly involved in academic administration activities. The results of the study indicate that innovations are used in the academic service administration of the Islamic Education Management Department, namely the use of SALAM facilitated by the University and the use of Google Forms as a tool to assist correspondence. Another innovation that can be implemented in post-pandemic academic administration is Hybrid, which combines online and offline administration systems. The implementation of these innovations has resulted in a more effective and efficient academic administration service system.